Pengaruh Corporate Governance, Financial Indicators, Dan Ukuran Perusahaan Terhadap Financial Distress - Nila, Intan (COMPETITIVE, 2021)
This study aims to determine the effect of corporate governance, financial indicators, and company size on financial distress. Corporate governance in this study uses managerial ownership and institutional ownership indicators. For financial indicators using liquidity, leverage, and profitability. And the last one uses company size.The study took samples of manufacturing companies listed on the Indonesia Stock Exchange (BEI). The sampling method was nonprobability, and the sampling technique used purposive sampling. The data was collected using secondary data in the form of annual financial reports obtained from the official website of the Indonesia Stock Exchange, namely www.idx.co.id. The number of company lists that were processed was as many as 54 companies, and the number of samples that met the criteria for this study were 16 companies so that 80 observational data were obtained. The financial distress criteria in this study are measured using the interest coverage ratio. This study uses multiple linear regression as data analysis. The results of this study indicate that Managerial Ownership, Institutional Ownership, Liquidity, Leverage, Profitability, and Company Size have a significant influence on financial distress conditions. This study failed to prove the effect of managerial ownership, liquidity and profitability on the possibility of financial distress.